1993
DOI: 10.1111/j.1540-8159.1993.tb01600.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and Specificity of the Tilt Table Test in Young Patients with Unexplained Syncope

Abstract: 25 of the 44 patients (57%) developed a vasovagal response or became symptomatic after 13.8 +/- 5.7 minutes of HUT. Three of the 18 volunteers (17%) had a vasovagal response and became symptomatic after 9 +/- 3 minutes of HUT. There was no statistical difference among the four groups (with and without tilt induced vasovagal response) in terms of age and baseline hemodynamic data. The sensitivity of 20 minutes HUT was 57% and its specificity was 83%. The presyncopal hemodynamic response in patients with history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(23 citation statements)
references
References 11 publications
1
21
0
1
Order By: Relevance
“…641,642 Treatment should emphasize symptom awareness and avoidance of precipitating factors that might worsen the condition, such as dehydration, standing for prolonged periods of time, hot crowded environments, and diuretic intake. 624,629,643,644,647,648,651,652 and the specificity ranges from 83% to 100%. 624,643,652 Pediatric patients with episodes of V VS may exhibit convulsive movements during loss of consciousness that mimic epileptic seizures.…”
Section: Pediatric Syncope: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…641,642 Treatment should emphasize symptom awareness and avoidance of precipitating factors that might worsen the condition, such as dehydration, standing for prolonged periods of time, hot crowded environments, and diuretic intake. 624,629,643,644,647,648,651,652 and the specificity ranges from 83% to 100%. 624,643,652 Pediatric patients with episodes of V VS may exhibit convulsive movements during loss of consciousness that mimic epileptic seizures.…”
Section: Pediatric Syncope: Recommendationsmentioning
confidence: 99%
“…624,629,643,644,647,648,651,652 and the specificity ranges from 83% to 100%. 624,643,652 Pediatric patients with episodes of V VS may exhibit convulsive movements during loss of consciousness that mimic epileptic seizures. In children with syncope and convulsions on tilt-table testing, 64% exhibited cardiac asystole with pauses >3 seconds.…”
Section: Pediatric Syncope: Recommendationsmentioning
confidence: 99%
“…Accordingly, the sensitivity of the tilt test in our study was 75% and the specificity 90%. To our knowledge, there was only one study reported previously, by Fouad et al [8], concerning the sensitivity and specificity of the tilt test in the young population. In their study the sensitivity of the tilt test was 56.8% and the specificity 83.3%.…”
Section: Discussionmentioning
confidence: 92%
“…Forty-four percent had syncope, and of these, half became syncopal within the first 5 minutes of standing [14]; 12 controls remained standing for 14 minutes and none became syncopal. In studies of children with syncope the diagnostic accuracy of HUT varied between 57 % and 70 % [1,5,6,11].…”
Section: Diagnostic Assessment Of Syncope In Childhoodmentioning
confidence: 98%